Green Politics for a Better Earth - Mintu Mondal (Politicon : Jurnal Ilmu Politik, 2022)
Our blue planet provides immeasurable treasures for livelihood, and it is sensible and tolerant. We are degrading our living place for the benefit of material continuance. The material continuance gives us physical pleasures a lot. On the other hand, it creates an eroded future. In this regard, we raise the question of why we are pushing up the blue planet on the line of destruction. We have to take care of the Earth for a better future. For this cause, we have pursued a new paradigm of decision-making instrument as the 'Green Politics' to cope with the material continuance of gatherings. The Green politics question how the tangible exertion for happenings eroded our living places. Once more, it tries to maintain social justice in societies regarding Green political problems. The research paper has gone through reflective research methods.